Factors associated with delayed cardiac tamponade after cardiac surgery (2018)
Context: Cardiac tamponade (CT) following cardiac surgery is a potentially fatal complication and the cause of surgical reintervention in 0.1%-6% of cases. There are two types of CT: acute, occurring within the first 48 h postoperatively, and subacute or delayed, which occurs more than 48 h postoperatively. The latter does not show specific clinical signs, which makes it more difficult to diagnose. The factors associated with acute CT (aCT) are related to coagulopathy or surgical bleeding, while the variables associated with subacute tamponade have not been well defined. Aims: The primary objective of this study was to identify the factors associated with the development of subacute CT (sCT). Settings and Design: This report describes a case (n = 80) and control (n = 160) study nested in a historic cohort made up of adult patients who underwent any type of urgent or elective cardiac surgery in a tertiary cardiovascular hospital. Methods: The occurrence of sCT was defined as the presence of a compatible clinical picture, pericardial effusion and confirmation of cardiac tamponade during the required emergency intervention at any point between 48 hours and 30 days after surgery. All factors potentially related to the development of sCT were taken into account. Statistical Analysis Used: For the adjusted analysis, a logistical regression was constructed with 55 variables, including pre-, intra-, and post-operative data. Results: The mortality of patients with sCT was 11% versus 0% in the controls. Five variables were identified as independently and significantly associated with the outcome: pre-or post-operative anticoagulation, reintervention in the first 48 h, surgery other than coronary artery bypass graft, and red blood cell transfusion. Conclusions: Our study identified five variables associated with sCT and established that this complication has a high mortality rate. These findings may allow the implementation of standardized follow-up measures for patients identified as higher risk, leading to either early detection or prevention. © 2018 Annals of Cardiac Anaesthesia